2017
DOI: 10.1111/1751-2980.12496
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia/IL‐1α axis promotes gastric cancer progression and drug resistance

Abstract: The IL-1α/hypoxia axis may be a valuable target for diagnosis and treatment of GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Recently, a critical role for the IL-1 pathway, in relation to therapy, is emerging in different types of solid tumors [63][64][65][66]. Specifically, several studies proposed a role for IL-1 in the poor responses to EGFR blockade and radiotherapy [67] with consequent treatment failures.…”
Section: Il-1 and Resistance To Targeted Therapymentioning
confidence: 99%
“…Recently, a critical role for the IL-1 pathway, in relation to therapy, is emerging in different types of solid tumors [63][64][65][66]. Specifically, several studies proposed a role for IL-1 in the poor responses to EGFR blockade and radiotherapy [67] with consequent treatment failures.…”
Section: Il-1 and Resistance To Targeted Therapymentioning
confidence: 99%
“…IL-1a, a key inflammatory cytokine, is frequently upregulated in a variety of cancers and it is shown to be associated with development, invasion, metastasis as well as prognosis of cancer. [19][20][21][35][36][37][38][39] It has been proposed that a functional 4-bp ins/del variant in the 3′UTR of IL1A alters miR-122 and miR-378 mediated regulation of IL-1α expression. 7,25,40 We designed a rapid and reproducible mismatch PCR-RFLP method for detection of 4-bp ins/del variant of IL1A gene.…”
Section: Discussionmentioning
confidence: 99%
“…Support for the role of hypoxia combined with inflammation in chemosensitivity is provided by Xuan and Wang (180), who showed that the inflammatory cytokine, IL-1a, was upregulated in gastric cancer during hypoxia and had a positive correlation with tumour stage, lymph node metastasis and resistance to cisplatin (180). Huang et al (181) showed that HIF-1a stimulates COX-2 expression, invasion, metastasis, and EMT after transcatheter arterial chemoembolisation treatment in hepatocellular carcinoma patients, which contributed to poor prognosis (181).…”
Section: Hypoxia and Inflammation Crosstalk In Cancer Treatmentmentioning
confidence: 99%